Comparison of Outcome of Transurethral Resection of Prostate Between Patients With Preoperative Low or Normal and High Voiding Pressure (Bangladesh Journal of Urology, 2020)
Objective: T0 compare the outcome of Transurethral Resecton of Prostate between Patients with Preoperative Low or Normal and High Voiding Pressure.Methods: This hospital based prospective observational study was conducted in the Department of Urology of Dhaka Medical college Hospital from July 2008 to June 2010 on male patients aging >59 years having Lower urinary tract symptoms (LUTS) attending to urology OPD& IPD were evaluated by history, physical examination including DRE and necessary investigations like USG of KUB and prostate with MCC & PVR, Q max, IPSS score to identify the potential candidates for TURP. Potential participants were counseled for urodynamic study. Who fulfilled the selection criteria included in this study in outpatient basis or admitted in the urology ward and numbered chronologically and performed urodynamic study and then patients underwent TURP, after 12 weeks of completion of TURP again a follow-up urodynamic study performed in all patients to compare the outcome between two groups. Sample size was 65, high pressure voiding group were 36 in number and Normal or low pressure voiding group were 29 in number. Data were collected on variables of interest using a structural data collection format. Data were processed and analyzed using SPSS (Statistical package for social science) software program. The test of significant employed to analyze the data was descriptive statistics and Student’s t-test, Paired and unpaired t- test, Fisher exact test. Probability value (P value < 0.05) was considered significant.Results: In this study the age ranges were 59 and 88 years and mean age was 70.7 ± 6.7 years. the maximum urinary flow rate, residual urine volume and maximum intravesical pressure 3 months after transurethral prostatic resection were significantly better in patients with high detrusor pressure compared to those with normal/low normal/low detrusor pressure (15.9±0.7 vs. 21.3±2.2ml/sec, p